Development and psychometric properties of the tool for assessing LGBTQI+ health training (TALHT) in pre-licensure nursing curricula. (March 2022) - Sherman, Athena D.F.; Klepper, Meredith; Claxton, Aubrey; Deng, Angie; Ling, Catherine; Mollenkopf, Nicole L.; Bower, Kelly
Abstract: Background: There is a lack of comprehensive lesbian, gay, bisexual, transgender, queer, and intersex (LGBTQI+) content in pre-licensure nursing curricula. LGBTQI+ people commonly experience mistreatment from nurses and healthcare providers due to a lack of knowledge or personal biases. To date, few instruments exist to guide LGBTQI+-specific curricular improvement. Objectives/design/setting/participant/methods: Johns Hopkins School of Nursing LGBTQI+ Health Initiative and Emory University School of Nursing developed the Tool for Assessing LGBTQI+ Health Training (TALHT) to assist in evaluating gaps and redundancies in LGBTQI+ health content within pre-licensure nursing curricula. Face and content validity were evaluated among experts in LGBTQI+ health, curricular development, nursing education, and measure development ( N = 22). The TALHT was modified based on expert feedback and a pilot with pre-licensure faculty ( N = 13) to evaluate utility and acceptability of the refined measure. Results: Face and content validity evaluation of the 60-item iteration of the TALHT showed that the majority of items were consistently relevant among external expert reviewers. However, the clarity and readability of items were lacking. We triangulated the quantitative and qualitative data from experts to adapt and reduce the number of items in the TALHT to 20 items. Pilot testing of the revised 20-item measure found that utility and acceptability of the tool were rated highly among pre-licensure faculty. Conclusion: The validation of the TALHT comes at a time when this type of instrument is clearly needed. The Future of Nursing 2020–2030 report calls for nursing education to incorporate competencies in caring for diverse populations to promote health equity. The Essentials: Core Competencies for Professional Nursing Education calls for a transition to operationalization of competency-based nursing education. The TALHT provides faculty and programs with a valid and reliable means to operationalize implementation of those competencies as they pertain to LGBTQI+ health. Highlights: Significant gaps in LGBTQ+ health coverage in nursing education exist. Few instruments exist to guide LGBTQI+ specific curricular integration in nursing. TALHT provides a valid and reliable means to address LGBTQI+ health competencies.